Pengaruh Penggunaan Media Big Book terhadap Kesulitan Membaca Permulaan Peserta Didik Sekolah Dasar - Nurdiana, Desi Eva; Liansari, Vevy (Dawuh Guru: Jurnal Pendidikan MI/SD, 2024)
This study aims to explore the effect of using Big Book media on the difficulties of beginning reading of elementary school students. This research was conducted with a focus on how the use of Big Book as a learning media can affect the learning process of beginning reading. In this research method using quantitative methods with the type of research used is Pre-experimental with One Group Pretest posttest Design desaign. One Group Pretest-Posttest is a study that first conducted a Pretest. Pretest is used to determine the difficulty of students' beginning reading before being given treatment and giving Postest after being given treatment. The purpose of giving Pretest and Postest is to accurately determine the results and as a comparison before and after being given treatment. The data collection technique used is a test, research instruments in the form of tests and documentation. The documentation method was used to obtain data on the list of students. While to analyse the data using the normality test (knowing the data obtained about normal or not), paired sample t-test. Data analysis techniques using normality test and hypothesis testing using Paired Sample T-Test. Data analysis techniques were carried out using normality tests and hypothesis testing using Paired Sample T-Test. Which resulted in a significance value of 0.000 ≤ 0.05 (Two-Tailed). The results show that Ho is rejected and Ha is accepted. The use of Big Book media has an effect on the initial reading difficulties of grade 1 students of SDN Wonoayu 2.